Control of Dendritic Cell Migration, T Cell-Dependent Immunity, and Autoimmunity by Protein Tyrosine Phosphatase PTPN12 Expressed in Dendritic Cells - Rhee, Inmoo (American Society for Microbiology, 2014)
Dendritic cells (DCs) capture and process antigens in peripheral tissues, migrate to lymphoid tissues, and present the antigens to T cells. PTPN12, also known as PTP-PEST, is an intracellular protein tyrosine phosphatase (PTP) involved in cell-cell and cell-substratum interactions. Herein, we examined the role of PTPN12 in DCs, using a genetically engineered mouse lacking PTPN12 in DCs. Our data indicated that PTPN12 was not necessary for DC differentiation, DC maturation, or cytokine production in response to inflammatory stimuli. However, it was needed for full induction of T cell-dependent immune responses in vivo. This function largely correlated with the need of PTPN12 for DC migration from peripheral sites to secondary lymphoid tissues. Loss of PTPN12 in DCs resulted in hyperphosphorylation of the protein tyrosine kinase Pyk2 and its substrate, the adaptor paxillin. Pharmacological inhibition of Pyk2 or downregulation of Pyk2 expression also compromised DC migration, suggesting that Pyk2 deregulation played a pivotal role in the migration defect caused by PTPN12 deficiency. Together, these findings identified PTPN12 as a key regulator in the ability of DCs to induce antigen-induced T cell responses. This is due primarily to the role of PTPN12 in DC migration from peripheral sites to secondary lymphoid organs through regulation of Pyk2.